Serum Hs-CRP level and clinical significance of patients with stress ulcer caused by massive blood loss after trauma - Chen, Wen; Li, Xiaolan; Wang, Aitian; Hao, Yanyan; Zhang, Jianjun; Liang, Jingtao; Yang, Yunfei; Zhao, Hualing; Gao, Jingli (Cellular and Molecular Biology, 2022)
Stress ulcer refers to a specific type of irritation of the inner wall of the gastrointestinal tract that occurs rapidly due to acute physiological stress such as severe disease, infection, or trauma. This study investigated the serum Hs-CRP level and clinical significance of patients with stress ulcers caused by massive blood loss after trauma. For this purpose, we studied 113 patients with enormous blood loss after trauma. During the study, 26 patients developed stress ulcers. Therefore, patients with massive blood loss after trauma were divided into two groups with and without stress ulcers. In addition to clinical and demographical evaluations, serum Hs-CRP levels were measured by ELISA test method in all patients at baseline, 6, and 12 days after starting the study. Results showed that 24 patients were excluded from the study due to termination of cooperation or death. Finally, 89 patients participated in the final analysis. Of these 89 patients, 26 developed stress ulcers. There was a significant difference between the two groups with stress and non-stress ulcers in terms of mean age (P=0.001) and gender (P=0.041). Also, there was a significant difference between the two groups regarding re-bleeding (P=0.012), the number of hospitalization days (P=0.001), and a decrease in hemoglobin (P=0.035). But there was no difference between the two groups regarding the need for re-surgery (P=0.276). The results of this study showed that increased serum hs-CRP levels are directly related to stress ulcers. Patients with higher serum Hs-CRP levels were more likely to develop stress ulcers than patients without stress ulcers during six days (P=0.04) and twelve days after starting the study (P=0.001). Current research results also show that the prevalence of stress ulcers occurs in men more than women. The risk of stress ulcers increases among older patients. People with stress ulcers also lose more hemoglobin, and finally, patients with more trauma and more extended hospital stays have a higher chance of developing stress ulcers.